2012
DOI: 10.1155/2012/434782
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Tannins and Flavonoids in Medicinal Plants: Evaluating Bioprospecting Strategies

Abstract: There are several species of plants used by traditional communities in the Brazilian semiarid. An approach used in the search for natural substances that possess therapeutic value is ethnobotany or ethnopharmacology. Active substances that have phenolic groups in their structure have great pharmacological potential. To establish a quantitative relationship between the species popularly considered to be antimicrobial, antidiabetic, and antidiarrheal, the contents of tannins and flavonoids were determined. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 49 publications
4
27
0
5
Order By: Relevance
“…This result was consistent with that discussed by Goleniowski et al [14] and de Barros et al [15]. This confirmed that antibiofilm activity can be related to the higher proportion of tannins and flavonoids in the plant like the observed by Siqueira et al [33]. …”
Section: Resultssupporting
confidence: 92%
“…This result was consistent with that discussed by Goleniowski et al [14] and de Barros et al [15]. This confirmed that antibiofilm activity can be related to the higher proportion of tannins and flavonoids in the plant like the observed by Siqueira et al [33]. …”
Section: Resultssupporting
confidence: 92%
“…For example, Araújo et al (2008) concluded that plants indicated for the treatment of inflammation have high levels of tannic compounds in comparison to plants indicated for other therapeutic uses. More recently, Siqueira et al (2012) found the same to be true of plants popularly listed as antimicrobials. Across habitats, Almeida et al (in press) found that medicinal plants harvested in the Caatinga exhibited higher antimicrobial activity than plants of the same species harvested in the Atlantic Forest.…”
Section: Patterns Trends and Perspectivesmentioning
confidence: 78%
“…A maior aplicabilidade do método de difusão radial encontra-se quando da necessidade de análise de um grande número de amostras, requisitada, principalmente, em estudos de triagem para seleção de plantas com potenciais atividades terapêuticas, e os que visam comparação de determinadas condições a que a espécie vegetal está submetida e como estas condições são refletidas no metabolismo secundário da planta Siqueira et al, 2011).…”
Section: Resultsunclassified